Quantitative correlation between carotid or lower limb atherosclerosis and coronary heart disease: a retrospective observational study - Jiang, Zeyu; Ruan, Shimiao; Zhao, Kun; Pan, Shuhan; Zhang, Wenzhong (Frontiers in Endocrinology, 2025)
BackgroundEarly diagnosis and intervention are key for the treatment of coronary heart disease (CHD). Ultrasound is used to assess risk stratification in patients with coronary artery disease. However, few studies quantify the relationship between carotid or lower limb atherosclerosis and coronary revascularization. The purpose of this study is to demonstrate that the semi-quantitative degree of atherosclerosis in the neck or lower extremity vessels can predict the need for coronary revascularization, thereby establishing a predictive model for coronary revascularization based on peripheral vascular disease.MethodsPatients who underwent coronary angiography and peripheral vascular ultrasound were randomly selected for semi-quantitative analysis of the degree of coronary artery and peripheral vascular stenosis. Data from 306 patients were collected.ResultsThe semiquantitative score, grade score and lower limb score from vascular ultrasound were positively correlated with the Gensini score of coronary artery lesions. The semi-quantitative score (score = 2) predicted the sensitivity and specificity for coronary revascularization at 83.74% and 61.72%, respectively. The graded score (score = 2) predicted the sensitivity and specificity for coronary revascularization at 77.24% and 72.13%, respectively. The lower extremity score (score = 3) predicted the sensitivity and specificity for coronary revascularization at 90.24% and 54.55%, respectively.ConclusionsCarotid semiquantitative scores, grade scores, and lower limb scores are predictive factors for the need for coronary revascularization and can serve as auxiliary examinations for the early diagnosis of coronary artery disease.